PENGAMBILAN KEPUTUSAN HUBUNGAN KERJA TERHADAP PERUSAHAAN SHOPEE INDONESIA - Dian Sudiantini; Ananda Ummu Thoyibah; Awalia Romadon; Muhammad Fauzan Zaen; Risma Indah Sari; Yudho Hari Rahmat (CV SWA Anugrah, 2023)
Making employment decisions for a company is the process of selecting an alternative to ensure the sustainability of the company. In this process, the company must consider internal and external factors that influence decision making. Research objectives With this research, it is hoped that in the future the decision-making process of the decision-making board can be better and in accordance with existing concepts, based on the company's conditions, so that for the future the company can continue to develop. The research method uses a qualitative data approach. Data collection was carried out by analyzing available data from journals, websites and research articles. This data was analyzed comprehensively to gain an in-depth understanding of employment relationship decision making in this company. Good decisions on employee recruitment, retention, development and management contribute significantly to company performance and image. Making the right decisions will have positive impact on company and employee performance.